Guidance Services for Bilingual Education - Guttman, Mary Alice Julius (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper outlines the development of a new bilingual programming (French immersion) for our schools. It documents the lack of development of adequate guidance service for these programs and presents a needs assessment for the development of guidance and counselling services. It provides a rationale why counsellors should address the following issues in bilingual education: (a) the need for guidance services in elementary schools, (b) the need for additional guidance services in secondary schools, (c) the need for training of fully qualified bilingual counsellors, and (d) the need for in-service training of all counsellors in French immersion schools.